A case of imported COVID-19 diagnosed by PCR-positive lower respiratory specimen but with PCR-negative throat swabs. Issue 6 (2nd June 2020) - Hase, Ryota; Kurita, Takashi; Muranaka, Emiri; Sasazawa, Hiroki; Mito, Haruki; Yano, Yudai
Abstract: A 35-year-old woman presented with fever and mild diarrhoea without any respiratory symptoms 9 days after travelling to Japan from Wuhan, China. Her computed tomography scan revealed pneumonia. The first polymerase chain reaction (PCR) test on throat swab for the novel corona virus upon admission was negative. Therefore, she was treated for community-acquired pneumonia, but fever persisted. On hospital day 5, PCR test on induced sputum was positive, but a second polymerase chain reaction test on throat swab remained negative. She was discharged, fully recovered, on hospital day 12. A lower respiratory tract specimen should be obtained for better diagnosis of corona virus disease 2019, even in the absence of respiratory symptoms for patients with significant travel or exposure history.